EFFICIENCY IN EXPRESSION: A COMPARATIVE STUDY OF ABBREVIATION USAGE IN THE UZBEK AND RUSSIAN LANGUAGES WITHIN THE MEDIA LANDSCAPE - Mutabarjon Kamolovna Sharipova (European Journal of Humanities and Educational Advancements, 2023)
This article presents an in-depth examination of the role of abbreviations in the Uzbek and Russian languages, with a special emphasis on their usage in the media context. The study explores the formation, application, and implications of abbreviations, offering a comparative analysis of these phenomena in the two languages. Drawing on specific examples from media outlets, the paper underscores how abbreviations not only economize communication but also facilitate brand recognition and enhance cultural significance. The analysis further suggests that the use of abbreviations in both languages is continually evolving, driven by technological advances, societal shifts, and changing communication practices. In essence, the study highlights the importance of understanding abbreviations for language learners, linguists, and media professionals, emphasizing the dynamic interplay of language, society, and culture.